2003
DOI: 10.1002/hpm.690
|View full text |Cite
|
Sign up to set email alerts
|

Costs of maternal health care services in three anglophone African countries

Abstract: This paper is a synthesis of a case study of provider and consumer costs, along with selected quality indicators, for six maternal health services provided at one public hospital, one mission hospital, one public health centre and one mission centre, in Uganda, Malawi and Ghana. The study examines the costs of providing the services in a selected number of facilities in order to examine the reasons behind cost differences, assess the efficiency of service delivery, and determine whether management improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
88
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(108 citation statements)
references
References 5 publications
12
88
8
Order By: Relevance
“…Furthermore, our study showed similar average costs of STI treatment as those reported by Daly et al (1998) in Malawi. The results of our study, however, revealed lower costs of RH interventions than those reported by Levin et al (2003) in three Anglophone countries (Uganda, Malawi and Ghana). We attribute the differences in the costs of RH interventions to the different methodological approaches used in the two studies.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our study showed similar average costs of STI treatment as those reported by Daly et al (1998) in Malawi. The results of our study, however, revealed lower costs of RH interventions than those reported by Levin et al (2003) in three Anglophone countries (Uganda, Malawi and Ghana). We attribute the differences in the costs of RH interventions to the different methodological approaches used in the two studies.…”
Section: Discussioncontrasting
confidence: 90%
“…Although the measurement of unit cost and coverage of interventions are critical in the processes of setting priorities and allocating resources efficiently, to date, only few studies have been conducted on costs of RH-maternal health care in developing countries, especially in sub-Saharan Africa (Levin et al 2003). Estimating costs of RH care can provide valuable information on how adequately these services are funded as well as on the efficiency of the interventions (Borghi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…12 The Directorate of District Health Services centrally monitors and coordinates the health manpower. An assessment of maternal health services in Masaka District 13 indicated that although health services in the district are of acceptable quality and sufficient demand exists for them, access to health facilities is limited. Only about 49% of the district population lives within five kilometres to a facility.…”
Section: District Health Profilementioning
confidence: 99%
“…Only 30% of childbirths are attended by trained health providers. 13 There are various levels of care that deliver safe motherhood interventions.…”
Section: District Health Profilementioning
confidence: 99%
“…Evidence from sub-Saharan Africa and South Asia indicates that households often spend significant amounts for delivery care (Nahar & Costello 1998;Levin et al 2000), especially if complications arise. Hospital costs associated with a dystocia case accounted for 34% of annual household income in Benin (Borghi et al 2003).…”
Section: Introductionmentioning
confidence: 99%